Elasticity modules and acoustic properties of metal ceramics on the basis of tungsten monocarbide; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 2 - Botaki A. A. (Mathematics and mechanics.Physics, 2007)
Заглавие с титульного листа